Application Analysis of Prefabricated Highrise Building Construction - Cai Hanying, (Forest Chemicals Review, 2021)
This paper analyzes the application of prefabricated high-rise building construction. Based on the quality of prefabricated buildings, this paper studies the theory and practice of quality management in manufacturing and construction industry at home and abroad. Based on the background of "integration of two modernizations", this paper combs the relevant research results of intelligent information transmission and collaborative management, and makes an in-depth study on the quality problem and improvement mechanism of prefabricated buildings as the core problem. This paper analyzes the performance and causes of quality problems in the construction process of prefabricated buildings by using arrangement diagram method and 4M1E method. This paper puts forward the quality problem improvement mechanism from four aspects: organization, culture, process control, technical guarantee and information collaborative management.